2021
DOI: 10.1136/jnnp-2021-326166
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic stroke on anticoagulation therapy and early recurrence in acute cardioembolic stroke: the IAC study

Abstract: Background and purposeA subset of ischaemic stroke patients with atrial fibrillation (AF) have ischaemic stroke despite anticoagulation. We sought to determine the association between prestroke anticoagulant therapy and recurrent ischaemic events and symptomatic intracranial haemorrhage (sICH).MethodsWe included consecutive patients with acute ischaemic stroke and AF from the Initiation of Anticoagulation after Cardioembolic stroke (IAC) study from eight comprehensive stroke centres in the USA. We compared rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 32 publications
7
61
0
Order By: Relevance
“…Due to this development, the number of patients with AF suffering a stroke despite anticoagulation is expected to increase, too 6 7. Accumulating evidence suggests that patients with AF and stroke despite anticoagulation are at a higher risk for future recurrence than patients who were naive to anticoagulation treatment before stroke 8–10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this development, the number of patients with AF suffering a stroke despite anticoagulation is expected to increase, too 6 7. Accumulating evidence suggests that patients with AF and stroke despite anticoagulation are at a higher risk for future recurrence than patients who were naive to anticoagulation treatment before stroke 8–10…”
Section: Introductionmentioning
confidence: 99%
“…For stroke physicians, ischaemic stroke despite anticoagulation in patients with AF represents a challenge in everyday clinical practice, as its aetiology is not well-understood 11. Competing stroke mechanisms such as large artery and small vessel disease, as well as non-adherence or inappropriately dosed anticoagulation have been discussed as potential causes of stroke despite anticoagulation,8–11 but few data on their relative frequency exist 6. A better understanding of the aetiology of stroke despite anticoagulation is needed to inform strategies to prevent recurrence after a stroke despite anticoagulation 11.…”
Section: Introductionmentioning
confidence: 99%
“…Seiffge et al could not find a beneficial effect of DOAC switching in their large meta-analysis, but this could be due to limitations in the external validity of the underlying original data regarding this specific topic [ 6 ]. Even after adjusting for pertinent confounders, the recent IAC study found no evidence of a beneficial effect [ 26 ]. Rather, AIS despite OAC appears to be an independent risk factor for future events that is poorly controlled by any OAC continuation alone [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite sufficient medication, some patients suffer from cerebral ischemic strokes of the suspected cardioembolic origin ( 4 ). These patients are at higher risk for further stroke recurrence ( 4 , 5 ), which illustrates the importance of a better pathophysiologic understanding of these ischemic events despite therapy, as reasons for that are not clarified yet. Phenomena, such as non-adherence to medication, genetic predisposition regarding drug effectiveness, or lastly another underlying stroke cause than the suspected cardioembolic origin have been discussed ( 4 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to an increased risk of stroke recurrence after an ischemic event despite anticoagulation for a suspected cardioembolic source ( 4 , 5 ), the important question remains which is the appropriate secondary prophylaxis for those patients. In the present study, the histologic and imaging characteristics of thrombi from patients with an acute ischemic stroke despite anticoagulation for treatment of a suspected cardioembolic source were analyzed and compared with suspected cardioembolic strokes without anticoagulation as well as patients with non-cardioembolic stroke.…”
Section: Introductionmentioning
confidence: 99%